A mixture of extracts from Peruvian plants (black maca and yacon) improves sperm count and reduced glycemia in mice with streptozotocin-induced diabetes - Gonzales G.F. (2013)
We investigated the effect of two extracts from Peruvian plants given alone or in a mixture on sperm count and glycemia in streptozotocin-diabetic mice. Normal or diabetic mice were divided in groups receiving vehicle, black maca (Lepidium meyenii), yacon (Smallanthus sonchifolius) or three mixtures of extracts black maca/yacon (90/10, 50/50 and 10/90%). Normal or diabetic mice were treated for 7 d with each extract, mixture or vehicle. Glycemia, daily sperm production (DSP), epididymal and vas deferens sperm counts in mice and polyphenol content, and antioxidant activity in each extract were assessed. Black maca (BM), yacon and the mixture of extracts reduced glucose levels in diabetic mice. Non-diabetic mice treated with BM and yacon showed higher DSP than those treated with vehicle (p < 0.05). Diabetic mice treated with BM, yacon and the mixture maca/yacon increased DSP, and sperm count in vas deferens and epididymis with respect to non-diabetic and diabetic mice treated with vehicle (p < 0.05). Yacon has 3.05 times higher polyphenol content than in maca, and this was associated with higher antioxidant activity. The combination of two extracts improved glycemic levels and male reproductive function in diabetic mice. Streptozotocin increased 1.43 times the liver weight that was reversed with the assessed plants extracts. In summary, streptozotocin-induced diabetes resulted in reduction in sperm counts and liver damage. These effects could be reduced with BM, yacon and the BM+yacon mixture.